Band gap opening of graphene by doping small boron nitride domains - Fan, Xiaofeng (2013)
Boron nitride (BN) domains are easily formed in the basal plane of graphene due to phase separation. With first-principles calculations, it is demonstrated theoretically that the band gap of graphene can be opened effectively around K (or K′) points by introducing small BN domains. It is also found that random doping with boron or nitrogen is possible to open a small gap in the Dirac points, except for the modulation of the Fermi level. The surface charges which belong to the π states near Dirac points are found to be redistributed locally. The charge redistribution is attributed to the change of localized potential due to doping effects. The band opening induced by the doped BN domain is found to be due to the breaking of localized symmetry of the potential. Therefore, doping graphene with BN domains is an effective method to open a band gap for carbon-based next-generation microelectronic devices.